2002
DOI: 10.1002/ppp.430
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution seismic and ground penetrating radar–geophysical profiling of a thermokarst lake in the western Lena Delta, Northern Siberia

Abstract: High-resolution seismic and ground-penetrating-radar (GPR) data have been acquired over Lake Nikolay in the western Lena Delta in order to study the uppermost basin fill and the bordering frozen margins. GPR (100 MHz antenna pair) measurements were completed on the frozen lake and its permafrost margins, while high-resolution seismic data were acquired from the lake during open-water conditions in summer using a 1.5-11.5 kHz Chirp profiler. The combined use of the two profiling systems allows stratigraphic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 17 publications
1
77
0
3
Order By: Relevance
“…Several previous studies have shown the benefits of combining more than one geophysical technique for mapping permafrost (e.g., De Pascale et al, 2008;Hauck et al, 2004;Schwamborn et al, 2002); in this study the GPR and ERT data also provided complementary information that allowed for interpretations that would not have been possible by using only one of the two data sets. Of course, combining multiple techniques for inference compounds our estimate uncertainties.…”
Section: On the Complementary Nature Of The Geophysical Techniquesmentioning
confidence: 78%
See 1 more Smart Citation
“…Several previous studies have shown the benefits of combining more than one geophysical technique for mapping permafrost (e.g., De Pascale et al, 2008;Hauck et al, 2004;Schwamborn et al, 2002); in this study the GPR and ERT data also provided complementary information that allowed for interpretations that would not have been possible by using only one of the two data sets. Of course, combining multiple techniques for inference compounds our estimate uncertainties.…”
Section: On the Complementary Nature Of The Geophysical Techniquesmentioning
confidence: 78%
“…Electrical resistivity tomography (ERT) has also been widely applied in permafrost studies (Hauck et al, 2003;Ishikawa et al, 2001;Kneisel et al, 2000), the majority of which focus on mountain permafrost. By combining two or more geophysical methods complementary information can often be acquired raising the confidence in interpretations of permafrost characteristics (De Pascale et al, 2008;Hauck et al, 2004;Schwamborn et al, 2002). For example, De Pascale et al (2008) used GPR and capacitive-coupled resistivity to map ground ice in continuous permafrost and demonstrated the added value of combining radar and electrical resistivity measurements for the quality of interpretation of the data.…”
Section: Y Sjöberg Et Al: Geophysical Mapping Of Palsa Peatland Permentioning
confidence: 99%
“…Almost three quarters of the grid cells feature water fractions of less than 20 %. However, relatively shallow thermokarst lakes dominate in the LRD, which at least partly freeze to the bottom in winter (Schwamborn et al, 2002a;Antonova et al, 2016), so microwave emission becomes similar to land areas, although in particular the wavelength dependency of the effect may be complex (Gunn et al, 2011). Furthermore, the winter discharge of the Lena River is very low compared to other northern rivers, as the catchment is largely located in the continuous permafrost zone (Yang et al, 2002).…”
Section: Snowmentioning
confidence: 99%
“…As in soils ͑e.g., Greaves et al, 1996;Huisman et al, 2003͒, the presence of liquid water can substantially alter the electromagnetic properties of the snow and produce high-amplitude reflections. GPR has been used in numerous arctic studies to image stratigraphy and other structures within snow ͑e.g., Sand and Bruland, 1998;Lundberg et al, 2000;Harper and Bradford, 2003;Marshall et al, 2007;Marshall and Koh, 2008;Bradford et al, 2009͒, subsurface geology and liquid water below snow and freshwater ice ͑e.g., Delaney et al, 1990;Arcone et al, 1992;Arcone et al, 1998;Schwamborn et al, 2002;Best et al, 2005͒, and sea-ice/seawater contact ͑e.g., Kovacs, 1977;Kovacs and Morey, 1992;Nyland, 2004;Bradford et al, 2008͒. Using GPR to detect oil deposited on snow or trapped at the base of the snowpack is substantially different than detecting oil within or beneath sea ice and requires alternate analysis and experimentation to verify its effectiveness. In particular, the electric-conductivity structure of snow differs substantially from that of sea ice.…”
Section: Basic Gpr Concepts For Oil Detection In Snowmentioning
confidence: 99%